KEMITRAAN BADAN PERMUSYAWARATAN DESA DENGAN KEPALA DESA DALAM PERCEPATAN PEMBANGUNAN DI DESA SUNGAI LINAU KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Umi Rahayu; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Sungai Linau Village, Siak Kecil Subdistrict, Bengkalis Regency with the aim to find out the Village Consultative Body Partnership with the Village Head in Accelerating Development as well as the factors that influence the partnership between the Village Head and BPD Sungai Linau Village, Siak Kecil District, Bengkalis Regency. The type of research used was descriptive qualitative, researchers used informants with informant retrieval using purposive sampling technique, the informants in this study were the Village Head of Sungai Linau, Head of the Sungai Linau BPD, Sungai Linau Village Head, and village communities. Research data collection techniques through observation, interviews, documentation and literature review. Analysis of data from the results of interviews and observations obtained are then recorded and collected so that it becomes a field note. The results of the study concluded that the village head with his device and BPD with residents in his area partnered with each other in developing the village. The BPD brings the aspirations of the community and together with the village head makes village regulations in realizing aspirations while overseeing the running of the village administration. Factors influencing the partnership between the Village Head and BPD of Sungai Linau Village, Siak Kecil Subdistrict, Bengkalis Regency, namely lack of transparency, lack of involvement of the BPD, lack of communication from Chief Village. For this reason, it is recommended to review concerning the system of accountability of the Village Head, increasing the capacity of individuals and organizations for BPDs, Village Heads and Village Secretaries and other village officials through continuous training. Good cooperation between the Village Government and other village institutions is needed, such as the Village Consultative Body and also with the community involved in it.Keywoard : Partnersip, Village Developme